2015
DOI: 10.1118/1.4931415
|View full text |Cite
|
Sign up to set email alerts
|

Automating linear accelerator quality assurance

Abstract: The performance of the TrueBeam Linac model was shown to be consistent based on automated analysis of trajectory log files and EPID images acquired during delivery of a standardized test suite. The results can be compared directly to tolerance thresholds. In addition, sharing of results from standard tests across institutions can facilitate the identification of QA process and Linac changes. These reference values are presented along with the standard deviation for common tests so that the test suite can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 25 publications
3
51
0
2
Order By: Relevance
“…The position which showed the largest error in the MLC width between slits coincided with the offset position. This is comparable to studies that showed that MLC position errors between slits were less than 0.5 mm at the offset position 18, 23. Hence, these results also indicate the effectiveness of the calibration method for the misaligned EPID geometry.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The position which showed the largest error in the MLC width between slits coincided with the offset position. This is comparable to studies that showed that MLC position errors between slits were less than 0.5 mm at the offset position 18, 23. Hence, these results also indicate the effectiveness of the calibration method for the misaligned EPID geometry.…”
Section: Discussionsupporting
confidence: 86%
“…Eckhause et al. examined whether or not a small MLC displacement (0.1–0.5 mm) could be detected by using EPID images (0.39 mm/pixel), and they were able to distinguish MLC deviations exceeding 0.3 mm, which is smaller than the EPID pixel size 18. Thus, subpixel estimation can be implemented using interpolated pixel values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, four sets of leaf positions are available for quantifying MLC performance [1][2][3][4][5][6][7][8][9][10][11] : (a) DICOM RT-plan's positions generated from treatment planning system; (b) EPID-acquired positions; (c) on-fly generated 4D Integrated Treatment Console (4DITC)-ordered positions; (d) actual positions read from the motor's encoder. Positions (c) and (d) are one-on-one recorded in LINAC-generated logs.…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous silicon electronic portal imaging device (EPID) has been used as a detector for linac QA measurements 2, 3, 4, 5, 6, 7, 8, 9, 10. EPID is well suited to a number of linac QA tests as it provides a high spatial and temporal resolution two‐dimensional digital measurement from a device that requires minimal setup time and is integrated into the linac.…”
Section: Introductionmentioning
confidence: 99%